Evaluating the effectiveness on the implementation of environmental management system for drainage system in Kajang, Selangor / Mohd Ridzuwan Abdullah - Abdullah, Mohd Ridzuwan (Faculty of Architecture, Planning and Surveying, 2013)
Water source is a very precious for all because it is a daily need of man as a domestic use for bathing, cooking and drinking. Based on Water Quality Index in Selangor, Hulu Langat is one of the drainages which have been contaminated. One of the main reasons is because of the waste disposal from industries nearby to Kajang area. Therefore, this study is conducted to identify problems in which contributes to drainage management in Kajang, Selangor. Besides, it is to study advantages of Environmental Management System for drainage management in Kajang and also to acknowledge and make comparison to used Environmental Management System for drainage management in Kajang. From the findings, it can be conclude that the implementation of EMS to organization especially factories giving more effective management to the organization. In addition, this EMS practices will give high benefits to environment in a long term subjected to drainage system focusing on river is highly contaminated day by days because of chemical waste from factories in Kajang area.